Interference management in 6G space and terrestrial integrated networks: Challenges and approaches - Yan, Shi; Cao, Xueyan; Liu, Zile; Liu, Xiqing (Intelligent and converged networks, 2020)
The Space-Terrestrial Integrated Network (STIN) is considered to be a promising paradigm for realizing worldwide wireless connectivity in sixth-Generation (6G) wireless communication systems. Unfortunately, excessive interference in the STIN degrades the wireless links and leads to poor performance, which is a bottleneck that prevents its commercial deployment. In this article, the crucial features and challenges of STIN-based interference are comprehensively investigated, and some candidate solutions for Interference Management (IM) are summarized. As traditional IM techniques are designed for single-application scenarios or specific types of interference, they cannot meet the requirements of the STIN architecture. To address this issue, we propose a self-adaptation IM method that reaps the potential benefits of STIN and is applicable to both rural and urban areas. A number of open issues and potential challenges for IM are discussed, which provide insights regarding future research directions related to STIN.